2011
DOI: 10.1111/j.1749-6632.2011.06237.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring intranodal pressure and lymph viscosity to elucidate mechanisms of arthritic flare and therapeutic outcomes

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease with episodic flares in affected joints, whose etiology is largely unknown. Recent studies in mice demonstrated alterations in lymphatics from affected joints precede flares. Thus, we aimed to develop novel methods for measuring lymph node pressure and lymph viscosity in limbs of mice. Pressure measurements were performed by inserting a glass micropipette connected to a pressure transducer into popliteal lymph nodes (PLN) or axillary lymph nodes (ALN) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Diffusion coefficient and lymph speed measurements were performed as described previously (Bouta et al . ). Briefly, a tunable mode‐locked Ti:Sapphire laser (Mai Tai; Spectra Physics, Mountain View, CA, USA), yielding 80‐fs pulses at a repetition rate of 100 MHz was used to monitor the sample at a low power while keeping focal volume consistent throughout the experiment.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Diffusion coefficient and lymph speed measurements were performed as described previously (Bouta et al . ). Briefly, a tunable mode‐locked Ti:Sapphire laser (Mai Tai; Spectra Physics, Mountain View, CA, USA), yielding 80‐fs pulses at a repetition rate of 100 MHz was used to monitor the sample at a low power while keeping focal volume consistent throughout the experiment.…”
Section: Methodsmentioning
confidence: 97%
“…Pressure measurements were performed as described previously (Bouta et al . ). Briefly, TNF‐Tg mice and their WT littermates (ages 4–10 months) were injected with 30 μl of 1% Evan's Blue (Sigma Aldrich) in the hind footpad for initial visualization the PLN.…”
Section: Methodsmentioning
confidence: 97%
“…In an effort to better understand the mechanism of PLN collapse, methods were developed to measure popliteal lymph node pressure (LNP), lymphatic pumping pressure (LPP) and lymph viscosity and speed [44, 45]. Multiphoton fluorescence after photobleaching (MP-FRAP) of injected FITC-BSA was used to calculate the lymph viscosity and speed [46].…”
Section: Measurement Of Lymph Node Pressure Lymphatic Pumping Prementioning
confidence: 99%
“…Mature LVs transport these factors and cells to lymph nodes. The draining function of the synovial lymphatic system can be monitored by numerous imaging modalities that we have developed, such as near-infrared lymphatic imaging to measure pluses/contraction and tracer clearance of mature LVs efferent joints [6,7]. Our ndings demonstrated that the synovial lymphatic system is closely related to the progression and are of arthritic joints, and its draining function is impaired in RA joints [8].…”
Section: Introductionmentioning
confidence: 80%